2021
DOI: 10.2196/29764
|View full text |Cite
|
Sign up to set email alerts
|

Digital Health Literacy in Bipolar Disorder: International Web-Based Survey

Abstract: Background Web-based resources can support people with bipolar disorder (BD) to improve their knowledge and self-management. However, publicly available resources are heterogeneous in terms of their quality and ease of use. Characterizing digital health literacy (the skillset that enable people to navigate and make use of health information in a web-based context) in BD will support the development of educational resources. Objective The aim of this stu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 72 publications
2
10
0
Order By: Relevance
“…Studies show that college students with low MHL lack the skills to be able to identify mental health problems and seek professional help when necessary [ 12 ]. Further evidence suggests that lack of digital literacy skills in mental health have negative consequences on mental health, due to failure to identify safe web-based resources to support their self-management [ 36 , 37 ]. eMHL, while not extensively studied, may be viewed as a facet of MHL, and includes the skills to access and appraise evidence-based internet-based mental health information and resources to aid in the recognition, management, or prevention of mental health issues.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies show that college students with low MHL lack the skills to be able to identify mental health problems and seek professional help when necessary [ 12 ]. Further evidence suggests that lack of digital literacy skills in mental health have negative consequences on mental health, due to failure to identify safe web-based resources to support their self-management [ 36 , 37 ]. eMHL, while not extensively studied, may be viewed as a facet of MHL, and includes the skills to access and appraise evidence-based internet-based mental health information and resources to aid in the recognition, management, or prevention of mental health issues.…”
Section: Discussionmentioning
confidence: 99%
“…Low digital skills in mental health influence in mental health outcomes. For example, some studies showed that lack of digital literacy skills have negative consequences for people with mental health disorders, because they fail to identify useful and safe web-based resources or tools with the potential to support their self-management [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Educational interventions to enhance digital health literacy may help individuals with BD to select the appropriate apps for their self-management goals. While in general, levels of digital health literacy are comparable for people with BD to the general population, a study found that individuals with BD who are younger, have completed less education, or are less familiar with mental health apps may require extra support to safely and productively navigate web-based health resources [ 39 ]. Recent steps have been taken to address the needs of these groups: a brief, informational video describing strategies to select safe, effective, and engaging mental health apps for BD was created [ 40 ], incorporating the perspectives of people with lived experience in the script and design.…”
Section: Improving the Dissemination And Uptake Of Apps For Bdmentioning
confidence: 99%
“…Although we aimed to make the PolarUs app as accessible as possible through community consultation, consideration of accessibility issues specific to serious mental health during the design phase [92], and attention to reading level in content writing, it is still likely that individuals with more familiarity with apps and computers will be better able to engage with the intervention and complete all required research tasks (ie, web-based questionnaires) [93]. Although it is not feasible for us to offer dedicated support to upskill participants in technological abilities in the context of this study, future research may evaluate whether adjunctive interventions can enhance the feasibility of mHealth interventions in populations with BD.…”
Section: Limitationsmentioning
confidence: 99%